Feeding selectivity of the invasive mussel Limnoperna fortunei (Dunker, 1857) on a natural phytoplankton assemblage: what really matters? - Frau, Diego (2016)
The aims of this work were to analyse the feeding selectivity of L. fortunei in a natural assemblage of phytoplankton in a short-term microcosm experiment and to assess whether this selectivity is affected by the presence of Rotifera as a secondary, palatable feeding resource. This bivalve preferred Desmidiales, Chlorococcales, Euglenophyceae and Chrysophyceae algae with a maximum linear dimension from 20 to 100 µm. Organisms between 500 and 40 × 103 µm3 belonging to Desmidiales, Chrysophyceae and Euglenophyceae were also positively selected. Volvocales, Cryptophyceae and one group of medium-size Euglenophyceae (Trachelomonas sp.) had a high, negative selectivity index independent of their cell shape or size (Ivlev’s index of feeding selectivity <−0.7). The mussel positively selected Rotifera, and this only had a measurable effect on large Euglenophyceae, which increase their selectivity value in the absence of Rotifera. The non-parametric multiplicative regression showed that selectivity is largely explained by a combination of cell shape, biovolume and the phytoplankton taxa offered (R2 > 0.8). We concluded that the impact on phytoplankton community structure could be severe, considering that the presence of zooplankton does not have an effect on the majority of phytoplankton groups and that the mussel tends to feed on both items to improve its diet. The negative selection of some phytoplankton taxa is possibly related to the morpho-physiological characteristics of their cell shells.